2018
DOI: 10.1002/anie.201801618
|View full text |Cite
|
Sign up to set email alerts
|

Affinity‐Driven Covalent Modulator of the Glyceraldehyde‐3‐Phosphate Dehydrogenase (GAPDH) Cascade

Abstract: Traditional medicines provide a fertile ground to explore potent lead compounds, yet their transformation into modern drugs is fraught with challenges in deciphering the target that is mechanistically valid for its biological activity. Herein we reveal that (Z)-(+)-isochaihulactone (1) exhibited significant inhibition against multiple-drug-resistant (MDR) cancer cell lines and mice xenografts. NMR spectroscopy showed that 1 resisted an off-target thiolate, thus indicating that 1 was a target covalent inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…This novel mechanism of action highlights the importance of GAPDH as a target for tumor treatment, since this mechanism bypasses the standard apoptosis-resistant route of MDR cancers. 205 GAPDH covalent inhibition occurs via Michael addition on the α-methylene lactone group, which was already described as a thiol reacting feature. 206 This warhead presents a finely modulated reactivity due to the electron-donating properties of the conjugated trimethoxyphenyl moiety; therefore, unspecific reactions with thiols were only sluggishly observed.…”
Section: Isochaihulactonesmentioning
confidence: 97%
See 3 more Smart Citations
“…This novel mechanism of action highlights the importance of GAPDH as a target for tumor treatment, since this mechanism bypasses the standard apoptosis-resistant route of MDR cancers. 205 GAPDH covalent inhibition occurs via Michael addition on the α-methylene lactone group, which was already described as a thiol reacting feature. 206 This warhead presents a finely modulated reactivity due to the electron-donating properties of the conjugated trimethoxyphenyl moiety; therefore, unspecific reactions with thiols were only sluggishly observed.…”
Section: Isochaihulactonesmentioning
confidence: 97%
“…203,204 In particular, the (S) enantiomer was found to be 7-10 times more active than its enantiomer, showing a 1 µM activity towards three different cancer cell lines. 205 In a very recent study using molecular probes, the non-catalytic Cys-247 of hGAPDH was identified as one of the main targets of (S)-13. The glycolytic activity of hGAPDH, which is mediated by the catalytic Cys-152, was not impaired.…”
Section: Isochaihulactonesmentioning
confidence: 99%
See 2 more Smart Citations
“…The key intermediate 2 a , for the synthesis of GPR109A analogs can be obtained in one step with good yield, which previously required five steps to prepare . Another key intermediate for the synthesis of a lignin derivative probe can be shortened from the previously reported four step synthesis to one step from commercially available 4‐methoxybenzaldehyde 1 d (Scheme ) . We envision that this efficient synthesis method may contribute to the preparation of nitrogen‐containing heterocyclic compounds, bioactive compounds, in the future.…”
Section: Resultsmentioning
confidence: 99%